Efficacy of doublesynch, estradoublesynch and progesterone based protocols for improving fertility in anoestrus Surti buffaloes - Dhami, Arjun J; Patel, Arpit J; Patel, J A; Prajapati, A R; Sarvaiya, N P (Indian Journal of Dairy Science, 2017)
This study was undertaken to find out the estrus induction and fertility response and monitor the peripheral plasma progesterone profile in 55 postpartum anoestrus buffaloes (>90 days) treated with Doublesynch, Estradoublesynch, PRID (Triu-B) and PRID + PMSG protocols (n=11 each), keeping a group of untreated anoestrus control (n=11). The induction of behavioural estrus in four protocols was 81.81, 90.90, 100.00 and 90.90 % within mean intervals of 64.77±2.19, 62.50±1.39, 61.45±1.34 and 64.00±1.25 hrs from PGF2α injection, respectively. The conception rates obtained at induced estrus with FTAI in above four protocols were 27.27, 27.27, 18.18 and 45.45 per cent, and overall of three cycles’ as 63.63, 54.54, 63.63 and 81.81 per cent, respectively. In untreated control group, only two buffaloes (20.00%) evinced estrus and conceived over a period of 90 days follow up. The mean plasma progesterone (P4, ng/ml) concentrations were low towards basal values (<0.5 ng/ml) on day 0 (i.e. day of initiation of treatment), but rose significantly (P<0.05) to the peak values on day 6/9 (just before PGF2α injection). Thereafter the levels dropped suddenly and significantly to the basal values at induced estrus, when FTAIs were done. These levels again increased significantly (P<0.05) on day 12 post-AI in all the groups, with apparently or significantly (P<0.05) higher mean plasma P4 (ng/ml) in conceived buffaloes as compared to non-conceived ones under Doublesynch (5.73±0.94 vs. 2.41±0.72), Estradoublesynch (4.15±0.61 vs. 2.90±1.09), PRID (4.39±0.20 vs. 1.61±0.49) and PRID + PMSG (6.32±0.69 vs. 4.46±1.20) protocols due to establishment of pregnancy in varying number of animals. Thus, it was concluded that all four estrus synchronization protocols established cyclicity and improved plasma progesterone profile post-treatment in majority of buffaloes, and many of them conceived at induced as well as subsequent cycles, proving their beneficial role in managing problem of postpartum anoestrus in buffaloes.